Randomised clinical trial: the long‐term safety and tolerability of naloxegol in patients with pain and opioid‐induced constipation. Issue 7 (12th August 2014) - Webster, L.; Chey, W. D.; Tack, J.; Lappalainen, J.; Diva, U.; Sostek, M.
Summary Background Opioid‐induced constipation (OIC) is a common adverse effect of opioid therapy. Aim To evaluate the long‐term safety and tolerability of naloxegol, an oral, peripherally acting μ‐opioid receptor antagonist (PAMORA), in patients with noncancer pain and OIC. Methods A 52‐week, multicenter, open‐label, randomised, parallel‐group phase 3 study was conducted in out‐patients taking 30–1000 morphine‐equivalent units per day for ≥4 weeks. Patients were randomised 2:1 to receive naloxegol 25 mg/day or usual‐care (UC; investigator‐chosen laxative regimen) treatment for OIC. Results The safety set comprised 804 patients (naloxegol, n = 534; UC, n = 270). Mean exposure duration was 268 days with naloxegol and 297 days with UC. Frequency of adverse events (AEs) was 81.8% with naloxegol and 72.2% with UC. Treatment‐emergent AEs occurring more frequently for naloxegol vs. UC were abdominal pain (17.8% vs. 3.3%), diarrhoea (12.9% vs. 5.9%), nausea (9.4% vs. 4.1%), headache (9.0% vs. 4.8%), flatulence (6.9% vs. 1.1%) and upper abdominal pain (5.1% vs. 1.1%). Most naloxegol‐emergent gastrointestinal AEs occurred early, resolving during or after naloxegol discontinuation and were mild or moderate in severity; 11 patients discontinued due to diarrhoea and nine patients owing to abdominal pain. Pain scores and mean daily opioid doses remained stable throughout the study; no attributable opioid withdrawal AEs were observed. Two patients in each group had an adjudicated major adverse cardiovascular event unrelated to study drug; no AEs were reported nor adjudicated as bowel perforations. Conclusion In patients with noncancer pain and opioid‐induced constipation, naloxegol 25 mg/day up to 52 weeks was generally safe and well tolerated.